HUBUNGAN STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DAN KINERJA ORGANISASI: STRATEGI ORGANISASI SEBAGAI VARIABEL MODERATING - Suharnomo, Suharnomo; Mas'ud, Fuad (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2005)
The research of Delery and Dotty (1996) concluded that the relationship between HRM strategy and organizational performance were not simple but complicated. The purpose of this research is to reexamine the relationship between HRM strategy and organizational performance by using organizational strategy as a contingent factor in that relationship. Respondents of the research were HRM managers of 81 companies which part of the Top Companies and Big Group in Indonesia, 71h Edition published by Compassindo. The big companies were considered to perform their HRM as a strategic partner (Nurhayati, 2001). The concepts of HRM strategy used in this research based on Bae and Lawler formulation (2000) and the organizational strategy based on Porter (1980). The result of this research shows, there is only one hypothesis supported (H1) of five dimensions of HRM strategy, namely fit between extensive training and differentiation strategy is highly correlated to its organizational performance (r = - 0.401, significant of p = 0.01). On the other hand, hypothesis H2, H3, H4, and HS are not supported. It means that differentiation strategy do not moderrate the relationship between empowering, staffing, performance based pay, broad design and organizational performance. There Is only one of five HRM strategy dimensions which is supporting contingency theory in HRM strategic literature, states that the relationship between HRM strategy and organizational performance is depend on the contextual factor, namely organizational strategy. The concept of fit between HRM strategy and organizational strategy will have a superior performance (Jackson & Sculer, 1995) needs to be explored in the future.